EFFECTS OF SINTERING PARAMETERS ON THE MICROSTRUCTURAL CHARACTERISTICS OF CU/CNTS NANOCOMPOSITES - Ali Samer Muhsan, Norani M Mohamed, Faiz Ahmad, Thar M Badri Alb, (2016)
Higher-powered electronics are being integrated into daily used devices rapidly. With these electronics, the need to remove the excessive heat generated from those devices effic iently and more economically became essential. In response to these critical needs, a unique nanocomposite materi al made of copper reinforced by carbon nanotubes was developed via powder injection molding technique (PIM). This wo rk aims to study the effect of different PIM sintering parameters on the microstructural characteristics of carbon nan otubes reinforced copper nanocomposites (Cu/CNTs). The effect of these parameters has a significant effect on the mech anical and thermal properties of the produced composites. For instance, the influences of varying the sintering dwell tim e on the densification process showed that short sintering dwell times (90 and 120 min at 1050 °C) were insufficient for a chieving complete sintered samples. Meanwhile, attempts were applied to increase the diffusion rate between the Cu part icles and CNTs by increasing the sintering dwell time up to 180 min at 1050 °C. The results showed a clear enhancement on t he densification process but led to a decomposition of the CNTs into amorphous carbon. The optimal sintering temperature f or achieving fully dense nanocomposite was optimized to be 1050 °C. Fully dense nanocomposite can provide large phon on mean free path inside the microstructure resulting high thermally conductive material